[Chest Tube in Thoracic Trauma - Recommendations of the Interdisciplinary Thoracic Trauma Task Group of the German Society for Thoracic Surgery (DGT) and the German Trauma Society (DGU)]. - Becker, Lars; Schulz-Drost, Stefan; Schreyer, Christof; Lindner, Sebastian (Zentralblatt für Chirurgie, 2023)
For unstable patients with chest trauma, the chest tube is the method of choice for the treatment of a relevant pneumothorax or haemothorax. In the case of a tension pneumothorax, needle decompression with a cannula of at least 5 cm length should be performed, directly followed by the insertion of a chest tube. The evaluation of the patient should be performed primarily with a clinical examination, a chest X-ray and sonography, but the gold standard of diagnostic testing is computed tomography (CT).A small-bore chest tube (e.g. 14 French) should be used in stable patients, while unstable patients should receive a large-bore drain (24 French or larger). Insertion of chest drains has a high complication rate of between 5% and 25%, and incorrect positioning of the tube is the most common complication. However, incorrect positioning can usually only be reliably detected or ruled out with a CT scan, and chest X-rays proofed to be insufficient to answer this question. Therapy should be carried out with mild suction of approximately 20 cmH2O, and clamping the chest tube before removal showed no beneficial effect. The removal of drains can be safely performed, either at the end of inspiration or at the end of expiration. In order to reduce the high complication rate, in the future the focus should be more on the education and training of medical staff members.
EVALuna2:561286